STRATEGY FOR EXPLORATION OF THE POTENTIAL OF THE REAL SECTOR ON REGIONAL ECONOMIC GROWTH IN PASAN DISTRICT, MINAHASA TENGGARA DISTRICT - Djawa, Djibrael; Ponggohong, Edryl Henok Prasetya; Rundengan, Margaretha; ponggohong, laurens (Asian Journal of Logistics Management, 2025)
The real sector is one of the sectors that triggers economic growth in a region.  Real sector growth is influenced by various factors, such as the availability of natural resources, investment, government policies, innovation and technology, as well as education and training, including in sub-district areas. Especially in Pasan District, which is the object of research for potential problems such as the agricultural sector: agricultural activities, plantations, forestry and fisheries;  Industry: includes processing of raw materials, production of semi-finished goods and finished goods; Mining: includes mining of minerals, such as gold, sand, stone;   . Tourism: includes tourist activities, accommodation and management of tourist destinations. Construction: includes the construction of infrastructure and buildings, especially those involving a large number of workers, and this sector has not been managed optimally.Thus, this research aims to find out strategies for exploring (exploring) the potential of the real sector for the regional economy, especially in Pasan sub-district, to find out the factors that influence real sector growth. And the contribution of the real sector to the rotation of the wheels of the economy. This research uses the qualitative descriptive method stage, namely the analysis of data obtained in the form of words, images or behavior, and not expressed in the form of numbers or statistical figures, but by providing an explanation or description of the situation or conditions studied in the form of a description.The research results show that the real sector potential of Pasan District which can improve the economy includes trading business activities such as Retail, Shops, Stalls, Culinary, Livestock and Traditional MarketsFactors that influence real sector growth on economic growth in Pasan sub-district. The number of existing businesses is around 112 businesses with 115 workers and a sales turnover of around 50 million per day which can turn the wheels of the economy in Pasan sub-district.With existing businesses you can make contributions to the government both in the form of paying taxes and helping in social activities.Keywords: Real sector, economic growth, industry, innovation, investment, technology